Serum autotaxin is a useful liver fibrosis marker in patients with chronic hepatitis B virus infection. Issue 4 (4th December 2017) - Joshita, Satoru; Ichikawa, Yuki; Umemura, Takeji; Usami, Yoko; Sugiura, Ayumi; Shibata, Soichiro; Yamazaki, Tomoo; Fujimori, Naoyuki; Komatsu, Michiharu; Matsumoto, Akihiro; Igarashi, Koji; Ota, Masao; et al.
Abstract : Aim: Autotaxin (ATX) is a secreted enzyme that is considered to be associated with liver damage as well as fibrosis. This study assessed the ability of ATX to diagnose liver fibrosis in patients with chronic hepatitis B virus (HBV) infection. Methods: Serum ATX levels were retrospectively evaluated in 101 treatment‐naïve patients with HBV‐related chronic hepatitis or cirrhosis, all of whom had undergone liver biopsy at our hospital. Results: Serum ATX concentration increased significantly according to liver fibrosis stage in overall (r = 0.46, P  < 0.0001), male (r = 0.55, P  < 0.0001), and female (r = 0.52, P  = 0.0006) patient groups. When analyzed by gender, serum ATX was one of the most reliable markers for all fibrosis stages compared with other tested non‐invasive markers, which included hyaluronic acid, type IV collagen 7S, aspartate aminotransferase‐to‐platelet ratio index, and fibrosis index based on four factors, according to receiver operating characteristic curve analysis. Conclusion: Based on this histologically proven data, ATX represents a novel non‐invasive biomarker for liver fibrosis in HBV‐infected patients.